Following NCCN guidelines within one hospital system in the United States: Comparison between cancer centers and genetic counselor utilization. Issue 2 (9th August 2021) - Powell, Karen; Rakestraw, Jonathan; Gupta, Sat; Shou, Wenhao; Lee, Kyung; Leitner, Ofri
Abstract: Genetic testing is an instrumental tool used to determine whether an individual has a predisposition to certain cancers. Knowing of a hereditary cancer predisposition may allow a patient and their family to consider high‐risk screening or risk‐reducing options. Genetic counselors work with physicians to identify patients at increased risk for genetic testing using available guidelines such as those provided by the National Comprehensive Cancer Network (NCCN). Information within one hospital system's cancer registry was used to identify individuals who qualify for genetic testing. This includes patients with a history of cancer of the breast (diagnosis ≤45, triple negative (TN) ≤60, and male), ovaries, colon (diagnosis ≤50), or uterus (diagnosis ≤50). Within this hospital system's registry, there are six cancer centers. Data were collected from cancer centers that utilized genetic counselors (GCs), and cancer centers that did not (non‐GC) to determine whether there was a difference in genetic testing rates between GC and non‐GC cancer centers. An analysis of 695 patients demonstrated a significantly higher proportion of eligible patients undergoing genetic testing at the GC cancer centers than at the non‐GC cancer centers (91.6% versus 68.7%, p  < .001). Further analysis of specific cancers showed a significantly higher uptake of genetic testing for eligible patients with colon cancer (90.8% versus 50%, p  < .001), breast cancer ≤45 (99.5% versus 86%, p  < .001), and ovarian cancer (91.3% versus 62.8%, p  < .001) at the GC cancer centers than at the non‐GC cancer centers. There was no significant difference in the proportion of testing of TN breast cancer ≤60 or uterine cancer ≤50 between cancer centers. These data suggest that having a GC working within a cancer center increases the ability to identify and offer testing to patients who meet NCCN genetic testing criteria based on their cancer type.